Association of the clinical profile and overall survival of pediatric patients with acute lymphoblastic leukemia - Correa, Bruno Terra; Silva, Gabriela Sales Serra; Mendes, Webert Joaquim Silva; Maia, Amanda de Moraes; Aleluia, Augusto Cezar Magalhães; Fonseca, Teresa Cristina Cardoso; da Guarda, Caroline Conceição; Gonçalves, Marilda de Souza; Aleluia, Milena Magalhães (Frontiers in Pediatrics, 2023)
Introduction: The clarification of etiopathology, the improvement of chemotherapy regimens and their risk stratifications, and the improvement in treatment support have increased the survival of children and adolescents affected by Acute Lymphoblastic Leukemia (ALL) past few years. This study aimed to estimate overall survival (OS) and event-free survival (EFS) in an onco-hematology treatment center in Brazil, reports the main clinical-laboratory characteristics of patients at diagnosis, verify the frequency of treatment-related adverse effects and the main causes of death. Material and methods: retrospective analysis involving patients diagnosed with ALL, treated with the protocol of the Brazilian Group for Treatment of Leukemias in Childhood (GBTLI), between 2010 and 2020 was carried out; the outcomes (relapse, deaths, development of new neoplasms) were analyzed SPSS® software was used for the statistical analyses, and the p-value was considered significant when less than 0.05 for all analyses. Results: 109 patients were included in the study; the median age was 5 years, with a slight predominance of males. Sixty-six patients were classified as high-risk (HR) group and 43 patients were classified as low-risk (LR) group. After 5 years of diagnosis, the OS was 71.5%, and the EFS was 65%. No statistical difference was found between the HR and LR groups for OS and EFS, while leukocyte counts were statistically associated with the outcome of death (p=0.028). Among the patients, 28 (25.6%) died due to infection accounting 46.4% of death causes. Among the 34 patients with unfavorable outcomes (death and/or relapse), 32 had no research for the minimal residual disease at the end of remission induction, and 25 were not investigated for the presence of chromosomal abnormalities. The most reported complications and treatment-related adverse effects were increased liver transaminases (85.9%), airway infection (79.4%), oral mucositis (67.2%), febrile neutropenia (64.4%), and diarrhea (36.4%). Conclusions: The rates of OS and EFS obtained in this cohort are similar to those obtained in the few previous similar studies in Brazil and lower than those carried out in developed countries. The unavailability of prognostic tests may have hindered risk stratification and influenced the results obtained.